PENAMBATAN MOLEKUL SIANIDIN Ipomoea batatas L. SEBAGAI INHIBITOR HUMAN EPIDERMAL RECEPTOR 2 (HER-2) PADA KANKER PAYUDARA - Ayubbi, Muhammad Reza Pahlevy Al; Melati, Rika; Karimah, Umul (Universitas Nahdlatul Ulama Kalimantan Timur, 2023)
HER-2 (Human Epidermal Receptor 2) is a receptor on the cell surface that affects cell proliferation, this receptor support controls healthy cell growth,divide and repair cells when they are damaged. When HER-2 had overexpressed will not controlled cancer cell division. Overexpressed HER-2 could inhibited with cyanidine compound flavonoid derivatives from Ipomoea batatas L. (purple sweet potato). This study aim to measured potential of Ipomoea batatas L. cyanidin compounds in inhibited overexpressed HER-2 using computational chemistry methods specifically is molecular docking. Stages of molecular docking receptor HER-2 is ligand set up with drew structure cyanidine with Marvin Sketch then optimized by Autodock Tools and Discovery Studio, lapatinib as a comparison ligand downloaded on PubChem website. HER-2 (3PP0) prepared with downloaded on Protein Data Bank website then optimized by Autodock Tools. Molecular Docking validated with docked protein target with native ligand by PyMOL to secured RMSD (root mean square deviation). Protein Targeted HER-2 docked with test ligand cyanidine, lapatinib, and native ligand by Autodock VINA, analysed energy bond and amino acid residue interactions by LigPlot+. Cyanidine had potency inhibitor of receptor HER-2 overexpressed from docked is had bound energy -7.1 ccal/mol up to -8.6 ccal/mol wich is also had amino acid residue interactions Met 801 equal to native ligand